Application of gelatin-coated magnetic particles for isolation of genomic DNA from bones - Pongsak Khanpetch (2018)
© 2015, Medical Association of Thailand. All rights reserved. Objective: To develop a method for human genomic DNA extraction from bone using gelatin-coated magnetic particles. Material and Method: Thirty human metacarpal with the bone age ranging from 36 to 93 years were included in the present study. Genomic DNA was extracted from bones using gelatin-coated magnetic particles. The concentration and purity of DNA were analyzed in comparison with a reference method. In addition, the quality of extracted DNA was examined for sex determination by conventional polymerase chain reaction (PCR). Results: The average DNA concentration using gelatin coated magnetic particles exhibited approximately 15 times higher than a reference method with an insignificantly difference of the DNA purity in both methods. Twelve (40%) and fifteen (50%) samples out of thirty DNA isolated using established and reference method, respectively, could be amplified and sex correctly determined by PCR. Conclusion: Gelatin coated magnetic particle is rapid, simple, and well-suited for isolation of DNA from bones.